THE HOREZU VALLEY - AN EXCELLENCY EUROPEAN DESTINATION - Romeo Cătălin CREŢU; Petrică ŞTEFAN; Petronela Georgiana COSTIN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
This study is the result of significant accumulation, made in a long series of initiatives and collaborations. The Partners for Local Development Foundation and partner communities from Horezu microregion, have joint activities by several years. These activities relates to education, training, facilitation of participatory strategic planning processes and animation of local development. Horezu Depression Association ADH (Intercommunity Development Association, whose members are Horezu city and rural comunity Costeşti, Măldăreşti, Slătioara and Vaideeni) initiated a program to develop local Horezu microregion. Their were joined mayors of Bărbăteşti, Franceşti Oteşani, Slătioara and Tomşani, FPDL Partners for Local Development Foundation, Resource Centre for Public Participation CeRe, Prefecture and County Council Vâlcea.